1974
DOI: 10.1042/bj1430115
|View full text |Cite
|
Sign up to set email alerts
|

Separation, purification and properties of β-lactamase I and β-lactamase II from Bacillus cereus 569/H/9

Abstract: 1. A procedure was devised which is suitable for the isolation of beta-lactamase I and beta-lactamase II from Bacillus cereus 569/H/9 on a large scale. After adsorption on to Celite both enzymes were eluted in good yield and separated by chromatography on Sephadex CM-50. 2. beta-Lactamase I was separated into three main components by isoelectric focusing and into two components by chromatography. 3. The Zn(2+)-requiring beta-lactamase II obtained by this procedure had a lower molecular weight (22000) than beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 32 publications
8
100
0
1
Order By: Relevance
“…Purchased bLA was further purified by HiTrap SP HP (GE Healthcare) equilibrated by 10 mM Tris HCl (pH 7) and 1 mM ZnCl 2 (24).…”
Section: Methodsmentioning
confidence: 99%
“…Purchased bLA was further purified by HiTrap SP HP (GE Healthcare) equilibrated by 10 mM Tris HCl (pH 7) and 1 mM ZnCl 2 (24).…”
Section: Methodsmentioning
confidence: 99%
“…Based on its kinetic parameters, ␤-lactamase BCL-1 belongs to group 2a of ␤-lactamases according to the BushMedeiros-Jacoby classification (7). IEF analysis showed that cultures of B. clausii NR gave multiple pIs ranging from 5.5 to 6, probably due to ragged amino termini, as shown for the ␤-lactamases produced by B. licheniformis 749/C (BL-␤L) (38) and B. cereus 569/H (␤-lactamase I) (13). IEF analysis of culture extracts of E. coli BL21(DE3)(pBCL-1) performed after 2 h of IPTG induction gave a major pI of 5.5.…”
Section: Resultsmentioning
confidence: 95%
“…Indeed, Colombo et al reported that YbxI of B. subtilis had a hydrolytic activity intermediate between those of penicillin-binding proteins and ␤-lactamases (12). Genomic analysis of B. clausii KSM-K16 showed that it does not seem to contain additional chromosomally encoded metallo-␤-lactamase in contrast to B. anthracis, which contains a gene encoding Bla2 (class B) in addition to a gene for Bla1 (class A) (9), or B. cereus, which contains a gene for BcII (class B) in addition to the BcI and BcIII (class A) genes (9,13).…”
Section: Resultsmentioning
confidence: 99%
“…The production of two inducible P-lactamases is unusual, although it has previously been reported for strains of Aeromonas spp. (13), Bacillus cereus (10), and Yersinia enterocolitica (8). Some Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%